Negative active layer and preparation method and application thereof

By designing the negative electrode active layer in a lithium-ion battery, the relationship between its thickness, tortuosity, particle size and compaction density is controlled, and the graphite material is magnetized to process the graphite negative electrode material volume expansion in lithium-ion batteries is solved, improving the rate performance and cycle life of the battery.

CN119812265AActive Publication Date: 2025-04-11ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411990558.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the volume of conventional graphite negative electrode materials changes greatly during charging and discharging, which affects battery performance. How to effectively alleviate volume expansion is an urgent problem.

Method used

A negative electrode active layer is proposed, which contains negative electrode active material. By controlling the relationship between thickness H, tortuosity τ, particle diameter D50 and compaction density P, it satisfies 1.6≤(H*τ)/(D*P)≤4.7, and combines magnetization treatment graphite material to optimize the arrangement structure of graphite.

Benefits of technology

By optimizing the structure of the negative electrode active layer, the diffusion path of lithium ions is reduced, the tortuosity of the electrode sheet is reduced, the rate performance of the battery and the electrolyte infiltration ability are improved, the expansion rate problem in the thickness direction of the battery is alleviated, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812265A_ABST
    Figure CN119812265A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode active layer and a preparation method and application thereof. A negative electrode active layer comprises a negative electrode active material containing a graphite crystal, the full width at half maximum of the 002 and 100 characteristic peaks of the graphite crystal is beta002 and beta100 respectively, the diffraction angles of the 002 and 100 characteristic peaks are theta002 and theta100 respectively, the average width La of the graphite crystal in the a-axis direction and the average height Lc of the graphite crystal in the c-axis direction are calculated, La = 1.77 lambda / (beta100 * cos theta100), K = 0.089, and # imgabs0 # Lc = (K * lambda) / (beta002 * cos theta002); wherein La / Lc is greater than or equal to 1 and less than or equal to 2.5. The condition that La / Lc is larger than or equal to 1 and smaller than or equal to 2.5 is met, more edge positions can be provided for intercalation / deintercalation of Li < + >, the diffusion path of Li < + > can be shortened, the rate performance can be improved, and the reversible capacity of graphite under the high current density is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a negative electrode active layer and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have outstanding advantages such as high energy density, no memory effect, long cycle life, fast charge and discharge, and low self-discharge. They are widely used in consumer electronics, electric vehicles, energy storage and other fields. In order to improve product competitiveness, one of the common methods is to increase battery energy density by using high-capacity negative electrode materials. Graphite is widely used in battery negative electrodes due to its high gram capacity. However, while conventional graphite brings high energy density, it usually shows a large volume change during charge and discharge, which affects the performance of the battery to a certain extent. Therefore, how to more effectively alleviate the volume expansion of negative electrode materials and ensure further improvement of battery performance is still a difficult problem that needs to be solved in the current lithium battery field. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a negative electrode active layer, which is used in a secondary battery, and has a low battery volume expansion rate and good battery safety performance.

[0004] The invention also provides a method for preparing the negative electrode active layer.

[0005] The invention also provides a negative electrode plate.

[0006] The invention also provides a secondary battery.

[0007] In a first aspect of the present invention, a negative electrode active layer is provided, wherein the negative electrode active layer contains a negative electrode active material, the thickness of the negative electrode active layer is H μm, the tortuosity of the negative electrode active layer is τ, and the negative electrode active material D is 50 Particle size Dμm, compaction density of negative electrode active layer P g / cm 3 The following conditions are satisfied: 1.6≤(H*τ) / (D*P)≤4.7.

[0008] The negative electrode active layer according to the embodiment of the present invention has at least the following beneficial effects:

[0009] Tortuosity is the ratio of the actual length of the seepage channel to the apparent length / macro distance through the seepage medium (which can be regarded as the thickness of the electrode or a value related to it). In the present invention, the tortuosity represents the degree of curvature of the porous electrode transmission path, that is, it is related to the ratio of the actual transmission path of lithium ions in the negative electrode active layer of the electrode to the thickness of the negative electrode active layer of the electrode. Therefore, the tortuosity has a certain correlation with the thickness of the electrode. The actual length of the seepage channel and the apparent length / macro distance through the seepage medium are deeply affected by the factors of P and D. Therefore, considering the battery energy density, electrochemical performance and other aspects, if 1.6≤(H*τ) / (D*P)≤4.7 is satisfied, the resulting battery can obtain better comprehensive performance.

[0010] Among them, the particle size of the negative electrode active material is closely related to the compaction density. The smaller the particle size of the material, the more conducive it is to the compaction density of the pole piece, thereby improving the battery energy density. In addition, the determining factors of ion diffusion tortuosity include the particle size, compaction density, and pole piece thickness of the material. Among them, large particle size, large compaction density, and thick pole piece will increase tortuosity and reduce the ion transmission efficiency. In the present invention, under the condition of satisfying 1.6≤(H*τ) / (D*P)≤4.7, the ion diffusion path is effectively shortened, the accumulation of ions on the surface of the negative electrode pole piece is reduced, and it is also helpful for the electrolyte to penetrate the negative electrode active layer, which can further increase the compaction density and pole piece thickness, thereby improving the energy density of the battery.

[0011] In some embodiments of the present invention, τ satisfies: 1.2≤τ≤2.5.

[0012] In some embodiments of the present invention, the tortuosity τ is calculated by the following formula:

[0013] τ=γε 1-ɑ

[0014] Among them, ε is the porosity of the negative electrode active layer, γ is 1, and ɑ is 1.5. ɑ is the Bruggeman index, and γ is the pore shape factor.

[0015] In some embodiments of the present invention, H satisfies: 5≤H≤100, such as 25≤H≤60.

[0016] In some embodiments of the present invention, D satisfies: 5≤D≤25, such as 11≤D≤17.

[0017] In some embodiments of the present invention, P satisfies: 1.55≤P≤1.85, such as 1.55≤P≤1.80.

[0018] In some embodiments of the present invention, the negative electrode active layer includes a negative electrode active material containing graphite, and the XRD spectrum of the graphite includes characteristic peaks (002) and (100); the half-height widths of the (002) and (100) peaks are β 002 , β 100 , the diffraction angles of (002) peak and (100) peak are θ 002 ,θ 100 ;

[0019] The average width of graphite along the a-axis is L a and the average height L along the c-axis c for:

[0020] L a =1.77λ / (β 100 *cosθ 100 ), L c =(K*λ) / (β 002 *cosθ 002 ), where K = 0.089,

[0021] And L a and L c Between: 1.4≤L a / L c ≤2.4.

[0022] a-axis: parallel to the surface of the graphite layer, usually called the edge plane (1010); c-axis: perpendicular to the graphite layer, representing the stacking direction between layers, usually called the basal plane (0001). Based on the XRD test spectrum of graphite crystal, L a The value represents the basal plane parallel to the graphite layer, L c The value represents the edge position of the graphite crystal end face. a ) compared to the edge position (L c ) has a higher Li + Insertion / extraction activity, resulting in higher rate performance. a The graphite exhibits a higher capacity. The present invention satisfies the condition: 1.4≤L a / L c ≤2.4, not only can Li + The embedding / extraction provides more edge positions and can shorten the Li +The diffusion path is more conducive to improving the rate performance and the reversible capacity of graphite at high current density. At the same time, satisfying this relationship has a certain improvement effect on the volume expansion rate of battery materials: the length of graphite material on the horizontal base plane is shorter, the anisotropy of the material in the negative electrode slurry coating process of the pole piece preparation will be more obvious, and the lithium insertion expansion of the material is decomposed from the Z direction to the X and Y directions, which can alleviate the thickness expansion of the battery.

[0023] In some embodiments of the present invention, the θ 100 42.8°~44.3°, θ 002 It is 23.0°~26.5°.

[0024] In some embodiments of the present invention, 20nm≤L a ≤100nm, 10nm≤L c ≤70nm, if optional, 30nm≤L a ≤80nm, 20nm≤L c ≤60nm.

[0025] In some embodiments of the present invention, the graphite includes at least one of natural graphite or artificial graphite. Optionally, the graphite contains graphite crystals.

[0026] In some embodiments of the present invention, the negative electrode active material further comprises at least one of a silicon material or a carbon material. Optionally, the negative electrode active material comprises at least one of a hard carbon or a silicon-carbon material. In some embodiments of the present invention, the negative electrode active material may include a negative electrode material containing graphite and silicon, or a mixed material containing graphite and hard carbon, or a mixed material containing graphite, a silicon negative electrode material and hard carbon. Optionally, the silicon negative electrode material may be silicon.

[0027] In some embodiments of the present invention, the negative electrode active layer further includes a conductive agent and a binder. The types of the conductive agent and the binder are not limited. For example, in some embodiments of the present invention, the conductive agent can be selected from one or more of SP, CNT, etc.; in some embodiments of the present invention, the binder can be selected from one or more of SBR, PAALi, etc.

[0028] In a second aspect of the present invention, a method for preparing a negative electrode active layer is provided, comprising the following steps: applying a negative electrode slurry containing graphite to a substrate surface to form a wet film, magnetizing, and drying to obtain the negative electrode active layer; the negative electrode active layer contains a negative electrode active material, and the thickness of the negative electrode active layer is H μm, the tortuosity of the negative electrode active layer is τ, and the negative electrode active material D is 50 Particle size Dμm, compaction density of negative electrode active layer P g / cm 3The relationship is satisfied: 1.6≤(H*τ) / (D*P)≤4.7. Optionally, the graphite includes but is not limited to one or more of natural graphite, artificial graphite and the like.

[0029] The method for preparing the negative electrode active layer according to the embodiment of the present invention has at least the following beneficial effects:

[0030] Graphite has a layered structure. Usually, lithium ions need to be inserted into the gaps in the graphite layers from the edge of the layered graphite, diffuse through the SEI film to the reaction site and combine with electrons. The tortuous route of lithium insertion and extraction is prone to lithium deposition. In the present invention, under the action of an external magnetic field, the electron spin in the graphite will change, and the electrons will rearrange, affecting the electronic structure and properties of the graphite, thereby changing the magnetization of the graphite. After magnetization, the arrangement direction of the graphite is changed to satisfy the relationship: 1.6≤(H*τ) / (D*P)≤4.7. Using it in lithium-ion batteries is more conducive to the insertion and extraction of lithium ions, reducing the tortuosity of the pole piece, improving the rate performance and electrolyte infiltration, reducing the thickness expansion during the battery cycle, alleviating the expansion problem in the thickness direction, and extending the battery cycle life.

[0031] In some embodiments of the present invention, the magnetic field strength of the magnetization is 3000-8000 Gs, such as 4000-6000 Gs.

[0032] In some embodiments of the present invention, the magnetization time is 3 to 30 seconds, such as 5 to 15 seconds.

[0033] In some embodiments of the present invention, the negative electrode slurry includes a negative electrode active material, and the negative electrode active material includes the graphite.

[0034] In some embodiments of the present invention, the negative electrode active material further comprises at least one of a silicon material or a carbon material. Optionally, the negative electrode active material comprises at least one of a hard carbon or a silicon carbon material. In some embodiments of the present invention, the negative electrode slurry may be a slurry containing graphite and a silicon negative electrode material, or a slurry containing a mixed material of graphite and hard carbon, or a slurry containing a mixed material of graphite, a silicon negative electrode material and hard carbon, etc.

[0035] In some embodiments of the present invention, the negative electrode slurry further includes a conductive agent.

[0036] In some embodiments of the present invention, the conductive agent includes at least one of conductive carbon black (SP) or carbon nanotubes (CNT). Optionally, the mass ratio of the SP to the CNT is (3-20):1.

[0037] In some embodiments of the present invention, the negative electrode slurry further includes a binder.

[0038] In some embodiments of the present invention, the binder comprises SBR and PAALi. Optionally, the mass ratio of SBR to PAALi is 1:(0.5-10).

[0039] In some embodiments of the present invention, in the negative electrode slurry, the mass ratio of the negative electrode active material, the conductive agent and the binder is (80-99.5):(0.1-10):(0.1-10), such as (90-99.5):(0.2-5):(0.3-5).

[0040] In some embodiments of the present invention, in the magnetizing step, the direction of the magnetic field used is not parallel to the wet film, such as optionally, the direction of the magnetic field is perpendicular to the wet film.

[0041] In some embodiments of the present invention, a magnetic bar is used to magnetize the wet film.

[0042] In some embodiments of the present invention, in the preparation method, the wet film is magnetized, dried, and compacted to obtain the negative electrode active layer.

[0043] In a third aspect of the present invention, a negative electrode plate is provided, wherein the negative electrode plate comprises the above-mentioned negative electrode active layer. In the present invention, the graphite arrangement orientation in the negative electrode plate is changed by magnetization, which is more conducive to the insertion and extraction of lithium ions, reduces the tortuosity of the plate, satisfies the relationship: 1.6≤(H*τ) / (D*P)≤4.7, improves the rate performance and electrolyte infiltration of the battery used in the negative electrode plate, and effectively alleviates the expansion rate problem in the thickness direction of the plate.

[0044] In some embodiments of the present invention, the negative electrode plate further includes a negative electrode current collector, and the negative electrode active layer is disposed on the surface of the negative electrode current collector.

[0045] In some embodiments of the present invention, the negative electrode active layer is disposed on at least one side of the surface of the negative electrode current collector.

[0046] According to a third aspect of the present invention, a secondary battery is provided, comprising the negative electrode plate described above.

[0047] In some embodiments of the present invention, the secondary battery includes at least one of a lithium ion battery or a sodium ion battery.

[0048] In some embodiments of the present invention, the secondary battery further includes a positive electrode sheet.

[0049] In some embodiments of the present invention, the positive electrode plate includes a positive electrode active material. The material type of the positive electrode active material is not limited. In some embodiments of the present invention, the positive electrode active material includes but is not limited to one or more of lithium cobalt oxide, ternary materials, lithium-rich materials or other positive electrode materials.

[0050] In some embodiments of the present invention, the secondary battery further comprises an electrolyte. The composition of the electrolyte is not limited. In some embodiments of the present invention, the electrolyte comprises an electrolyte salt and an organic solvent, wherein the specific types and compositions of the electrolyte salt and the organic solvent are not subject to specific restrictions, such as positive electrode film-forming additives, negative electrode film-forming additives, additives for improving circulation, and low-temperature additives.

[0051] In some embodiments of the present invention, the secondary battery further comprises a separator. The material of the separator is not limited. In some embodiments of the present invention, the separator comprises but is not limited to one or more of polyethylene, polypropylene, polyvinylidene fluoride, etc. and their multilayer composite films.

[0052] In some embodiments of the present invention, the secondary battery further includes a packaging film. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0054] The experimental methods without specific conditions in the following examples and comparative examples are generally based on conventional conditions in the art or conditions recommended by the manufacturers; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents available from commercial channels such as conventional markets.

[0055] Graphite: purchased from Jiangxi Zichen Technology Co., Ltd., material number: YP-APG-0058-0000; graphite can also be purchased from other manufacturers;

[0056] SBR, PAALi, and PVDF can be purchased from Yitong New Energy Materials Co., Ltd. (corresponding materials can be purchased from other manufacturers); among them, SBR material number: DM-GAS-0002-0077; PAALi material number: YP-GAA-0007-0000; PVDF material number: DM-GPK-0001-0007;

[0057] Conductive agent: purchased from Yitong New Energy Materials Co., Ltd., DM-GCN-0002-0138, slurry containing CNT and dispersant, water-based, black liquid or jelly-like slurry, slurry solid content 1.00±0.20, CNT content 0.40±0.15, dispersant content 0.60±0.15, viscosity 500~10000mPa·s;

[0058] Example 1

[0059] This embodiment discloses a negative electrode active layer, the preparation process of which includes the following steps:

[0060] The negative electrode active material graphite, conductive agent (SP and CNT mixed, mass ratio is 0.45:0.05), binder (SBR and PAALi mixed, mass ratio is 0.5:1.8) are mixed with solvent water in a weight ratio of 97.7:1.1:1.2 to prepare the negative electrode active material slurry (the solid content of the slurry is 65% to 80%). The negative electrode active material slurry is evenly coated on the surface of both sides of the negative electrode collector (copper foil with a thickness of 5μm) to obtain a wet film. During the wet film coating stage, the magnetic field force of the magnetic bar is used to magnetize the graphite on the wet film (the magnetic bar is set directly above the wet film, the magnetic field strength is 5000gs, and the magnetization time is 8s), and the magnetic field direction is perpendicular to the wet film. Then dry, cold press, and cut into strips to form a negative electrode active layer on the surface of the negative electrode collector.

[0061] This embodiment discloses a negative electrode plate, which is a plate formed by the negative electrode current collector of this embodiment and the negative electrode active layers prepared on its two side surfaces.

[0062] This embodiment discloses a lithium-ion battery, including the negative electrode plate and the positive electrode plate of this embodiment, an electrolyte and a separator.

[0063] Among them, the preparation method of the positive electrode plate includes: fully and evenly dispersing the positive electrode active material LiCoO2, acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solvent system in a weight ratio of 97.6:0.5:0.6:1.3 (the solid content of the slurry can be 50% to 80%), and coating them on both sides of the positive electrode current collector (aluminum foil with a thickness of 8μm).

[0064] Isolation membrane: A ceramic mixture is coated on the surface of a PE base membrane to form a ceramic layer to obtain a composite isolation membrane; the PE base membrane has a thickness of 4 μm, the ceramic layer is a ceramic layer formed by a mixed slurry of PVDF and Al2O3, and the total thickness of the composite isolation membrane is 6 μm.

[0065] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1.2:1:4:4 to obtain a mixed organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0066] The preparation of the lithium-ion battery includes: winding the above-mentioned negative electrode plate, separator, and positive electrode plate (in other embodiments, they can also be stacked) to produce a bare cell, encapsulating and injecting electrolyte to obtain a lithium-ion battery.

[0067] Examples 1 to 15 and Comparative Examples 1 to 2 disclose a series of negative electrode active layers, negative electrode plates and lithium ion batteries. Among them:

[0068] The only difference between the polar active layers of Examples 1 to 15 and Comparative Examples 1 to 2 and Example 1 is that the negative electrode active layer adopts the design parameters of Table 1, wherein the magnetization intensity (4000 to 6000 Gs) and the magnetization time (5 to 15 s) of each example are adjusted to obtain the negative electrode active layer of each example and each comparative example (strengthening the magnetic field intensity and extending the magnetization time will reduce the OI value of the pole piece graphite, which is conducive to the diffusion of lithium ions), and the other conditions are the same as Example 1.

[0069] The negative electrode sheets in Examples 1 to 15 and Comparative Examples 1 to 2 are different from Example 1 only in that the negative electrode active layers in Examples 1 to 15 and Comparative Examples 1 to 2 are used to replace the negative electrode active layer in Example 1, and the rest are the same as Example 1.

[0070] The lithium ion batteries in Examples 1 to 15 and Comparative Examples 1 to 2 are different from Example 1 only in that the negative electrode sheets in Examples 1 to 15 and Comparative Examples 1 to 2 are used to replace the negative electrode sheets in Example 1, and the rest are the same as in Example 1.

[0071] Table 1

[0072]

[0073] The calculation formula of tortuosity τ is:

[0074] τ=γε 1-α

[0075] Among them, ε is the porosity of the electrode, γ is 1, and ɑ is 1.5.

[0076] Pole porosity ε test: Use a mercury intrusion instrument, PoreMaster 60, to apply a pressure of about 0.6 to 50 PSI in the low-pressure station and 20 to 60,000 PSI in the high-pressure station. Use a cone probe made of glass as a sample container to apply pressure to the sample. The sample container has a volume of 0.5 cm and a length of 3.8 cm. The volume of mercury applied to the sample is the pore volume V. If the sample volume is assumed to be V 总 , then the porosity ε=V / V 总 *100%.

[0077] Test example

[0078] This test example performs performance tests on the batteries obtained in the examples and comparative examples, specifically including:

[0079] (1) Figure 1 This is the XRD spectrum of the negative electrode sheet of Example 1, in which the red peak represents the Cu current collector, the blue represents graphite, the (002) characteristic peak is around 26.5°, and the (100) characteristic peak is around 43°.

[0080] (2) Rate performance, including:

[0081] Charge to 4.5V at 0.5C constant current and constant voltage, with a cut-off current of 0.02C; leave for 0.5 hours; discharge to 3.0V at 0.2C constant current, and read the capacity C0.

[0082] Charge to 4.5V at 0.5C constant current and constant voltage, with a cut-off current of 0.02C; leave for 0.5 hours; discharge to 3.0V at 1.0C constant current, and read the capacity C1.

[0083] Rate performance = C1 / C0*100%.

[0084] (3) Cyclic testing, including:

[0085] In an environment of 25℃, the cycle test was carried out according to the following method. Charging mode: 2.7C CC to 4.25V, 2C CC to4.35V, CV to 1.8C, 1.8C CC to 4.4V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2CCC to 4.55V, CV to 0.25C; Discharging mode: 0.7C DC to 3.0V.

[0086] 500-week Fading = discharge capacity of the 500th week / discharge capacity of the 1st week * 100%;

[0087] 500-week Swelling = 500th week full-charge thickness / initial half-charge thickness * 100%;

[0088] All battery thicknesses are tested using 600PPG.

[0089] (4) Fluid retention test: Fluid retention = fluid injection - fluid loss.

[0090] The test results are shown in Table 2:

[0091] Table 2

[0092]

[0093] It can be seen from the embodiments and comparative examples that by magnetizing the negative pole piece, the negative pole piece satisfies the relationship: 1.6≤(H*τ) / (D*P)≤4.7, 1.4≤L a / L c Under the condition of ≤2.4, the rate performance of the battery is significantly improved, and the battery's liquid retention capacity is enhanced, providing a guarantee for long-cycle performance testing. When 1.6≤(H*τ) / (D*P)≤4.7 is met, lithium ions can be better embedded in the negative electrode sheet and can travel a shorter distance to reach the lithium insertion position, avoiding lithium ion accumulation on the negative electrode surface. a / L c ≤2.4, lithium ions can be more quickly inserted into graphite to complete the lithium insertion action, and the free lithium ions in the pole piece can be evacuated in time, which promotes the rate performance of the battery and improves the charging capacity. In addition, the battery cycle performance of the negative pole piece of the present invention is better, and the swelling in the late cycle is smaller, indicating that the expansion rate in the thickness direction is improved, which can better meet the market demand. Among them:

[0094] Compared with (H*τ) / (D*P)<1.6, under the condition of 1.6≤(H*τ) / (D*P)≤4.7, the ion diffusion path is effectively shortened, reducing the accumulation of ions on the surface of the negative electrode plate, and helping the electrolyte to penetrate the active material layer, which can further increase the compaction density and the plate thickness, thereby improving the energy density of the battery.

[0095] L a The value represents the basal plane parallel to the graphite layer, L c The value represents the edge position of the end face of the graphite crystal. Compared with the basal plane (La), the edge position (Lc) has a higher Li + Insertion / extraction activity, resulting in higher rate performance. Graphite with high La content exhibits higher capacity. Satisfying the condition: 1.4≤L a / L c ≤2.4, not only can Li + The embedding / extraction provides more edge positions and can shorten the Li + This is beneficial to improving the rate performance and the reversible capacity of graphite at high current density.

[0096] Therefore, the negative electrode plate of the present invention can significantly improve the rate performance and cycle performance of the lithium-ion battery, solve the problem of battery failure caused by large material expansion, and at the same time the battery cell also has improved liquid retention performance and energy density.

[0097] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values ​​2 and 3.

[0098] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A negative electrode active layer, characterized in that: The negative electrode active layer contains a negative electrode active material. The thickness of the negative electrode active layer is H μm, the tortuosity of the negative electrode active layer is τ, and the negative electrode active material D 50 Particle size Dμm, compaction density of negative electrode active layer P g / cm 3 The following conditions are satisfied: 1.6≤(H*τ) / (D*P)≤4.

7.

2. The negative electrode active layer according to claim 1, characterized in that The τ satisfies: 1.2≤τ≤2.5; and / or, the H satisfies: 5≤H≤100.

3. The negative electrode active layer according to claim 1, characterized in that: The D satisfies: 5≤D≤25; and / or, the P satisfies: 1.55≤P≤1.

85.

4. The negative electrode active layer according to claim 1, characterized in that: The tortuosity τ is calculated by the following formula: τ = γε 1-α Among them, ε is the porosity of the negative electrode active layer, γ is 1, and ɑ is 1.

5.

5. The negative electrode active layer according to claim 1, characterized in that: The negative electrode active material comprises graphite, wherein the XRD spectrum of the graphite comprises characteristic peaks (002) and (100); the half-height widths of the (002) and (100) peaks are β 002 , β 100 , the diffraction angles of (002) peak and (100) peak are θ 002 ,θ 100 ; The average width of graphite along the a-axis is L a and the average height L along the c-axis c for: L a =1.77λ / (β 100 *cosθ 100 ),L c =(K*λ) / (β 002 *cosθ 002 ), among which, K=0.089, And L a and L c Between: 1.4≤L a / L c ≤2.

4.

6. The negative electrode active layer according to claim 5, characterized in that: 20nm≤L a ≤100nm,10nm≤L c ≤70nm。 7. A method for preparing a negative electrode active layer according to claim 1, characterized in that: The method comprises the following steps: coating the negative electrode slurry containing graphite on the surface of the substrate to form a wet film, and then magnetizing and drying to obtain the negative electrode active layer.

8. The method for preparing a negative electrode active layer according to claim 7, characterized in that: The magnetic field intensity of the magnetization is 3000 to 8000 Gs; and / or, the magnetization time is 3 to 30 s; Preferably, in the preparation method, the wet film is magnetized, dried, and compacted to obtain the negative electrode active layer.

9. A negative electrode plate, characterized in that: The invention comprises the negative electrode active layer according to any one of claims 1 to 6 or the negative electrode active layer prepared by the preparation method according to any one of claims 7 to 8.

10. A secondary battery, characterized in that: The negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and device

    CN115917780A

  • Thick electrode with low tortuosity and preparation method and application thereof

    CN116387464A

  • Graphite anode and preparation method and application thereof

    CN116885103A

  • Negative active material, negative pole piece and secondary battery

    CN118538914A

  • Anode having high top layer sphericity

    US20220149340A1